TAP1-independent loading of class I molecules by exogenous viral proteins. - Bachmann, M; Oxenius, A; Pircher, H; Hengartner, H; Ashton-Richardt, P; Tonegawa, S; Zinkernagel, R (1995)
Presentation of peptides derived from endogenous proteins on class I molecules needs functional TAP peptide transporters. To reveal whether class I-associated presentation of exogenous proteins also required the presence of TAP transporters, we assessed in vitro the ability of spleen cells and macrophages from TAP1-deficient mice (TAP1-/-) to present peptides derived from exogenous recombinant viral proteins on their class I molecules. We found that recombinant glyco- and nucleoprotein from lymphocytic choriomeningitis virus and nucleoprotein of vesicular stomatitis virus were presented as efficiently by TAP1-/- cells as by control cells. Peptide regurgitation was not involved. Since particulate, non-replicating antigens can efficiently prime anti-viral cytotoxic T cells in vivo, this new, TAP-independent pathway of class I-associated antigen presentation may be applicable for vaccine strategies.